The rate of return to education in Malaysia service sectors - Suraya Mahmood; Nor Hafiza Othman (2014)
The purpose of this study is to examine the rate of retun for education amongst workers in service sectors (banking, insurance and financial institution) with 300 respondents were selected in Kuala Lumpur Area. This study used Mincer function and used variable years of schooling (s) and working experince (EXP) as a main variable to influence rate of return in labour market. Besides that, these research also using demography